2008
DOI: 10.1007/s00441-008-0585-9
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the role of FMRFamide-related peptides in the circadian clock of the cockroach Leucophaea maderae

Abstract: The accessory medulla, the circadian clock of the cockroach Leucophaea maderae, is abundant in neuropeptides. Among these neuropeptides are the FMRFamide-related peptides (FaRPs), which generally share the C-terminal RFamide. As a first step toward understanding the functional role of FaRPs in the circadian clock of the cockroach, immunocytochemistry with antisera against various FaRPs, MALDI-TOF mass spectrometry, and injections of two FaRPs combined with running-wheel assays were performed. Prominent FMRFami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
1
20
0
1
Order By: Relevance
“…Immunocytochemical and electron microscopic studies suggest that these neurons contain a rich variety of neuropeptides (Reischig and Stengl, 1996;Homberg et al, 2003). To date, leucokinin, pigment-dispersing factor (PDF), baratin, orcokinin, gastrin/CCK, allatotropin, and different FMRFamide-related peptides, such as leucomyosuppressin and short neuropeptide F have been detected by immunostaining in AMe neurons (Petri et al, 1995;Stengl, 1996, 2003b;Nässel et al, 2000;Hofer and Homberg, 2006a;Soehler et al, 2007Soehler et al, , 2008. Among these, anterior PDF-immunoreactive (-ir) neurons (aPDFMes) have been studied most intensively.…”
Section: Indexing Terms: Neuropeptides; Insect Brain; Circadian Rhythmsmentioning
confidence: 98%
See 1 more Smart Citation
“…Immunocytochemical and electron microscopic studies suggest that these neurons contain a rich variety of neuropeptides (Reischig and Stengl, 1996;Homberg et al, 2003). To date, leucokinin, pigment-dispersing factor (PDF), baratin, orcokinin, gastrin/CCK, allatotropin, and different FMRFamide-related peptides, such as leucomyosuppressin and short neuropeptide F have been detected by immunostaining in AMe neurons (Petri et al, 1995;Stengl, 1996, 2003b;Nässel et al, 2000;Hofer and Homberg, 2006a;Soehler et al, 2007Soehler et al, , 2008. Among these, anterior PDF-immunoreactive (-ir) neurons (aPDFMes) have been studied most intensively.…”
Section: Indexing Terms: Neuropeptides; Insect Brain; Circadian Rhythmsmentioning
confidence: 98%
“…Seven soma groups are associated with the AMe, totaling about 250 neurons. According to position relative to the AMe, they were termed anterior neurons (ANes), distal (DFVNes), and medial frontoventral (MFVNes) neurons, median neurons (MNes), ventral neurons (VNes), ventromedian (VMNes), and ventroposterior (VPNes) neurons Stengl, 1996, 2003b;Soehler et al, 2008). Immunocytochemical and electron microscopic studies suggest that these neurons contain a rich variety of neuropeptides (Reischig and Stengl, 1996;Homberg et al, 2003).…”
Section: Indexing Terms: Neuropeptides; Insect Brain; Circadian Rhythmsmentioning
confidence: 98%
“…These authors concluded there are many issues yet to be resolved regarding the roles of neuropeptides in the regulation of feeding behaviour. FLPs, including DRSDNFIRFa, have been implicated in the regulation of the circadian clock in the cockroach, Leucophaea maderae (Soehler et al 2008). Genome projects have been completed for several insects including D. melanogaster, D. pseudoobscura, A. gambiae, Aedes aegypti, Culex quinquefasciatus, Bombyx mori, Acyrthosiphon piscum, Nasonia vitripennis, Pediculuc humanus corporis and Apis mellifera (Adams et al 2000;Ashburner and Bergman 2005;Holt et al 2002;International Silkworm Genome Consortium 2008;Mita et al 2004;Pittendrigh et al 2006;Weinstock et al 2006;Sabater-Munoz et al 2006;Nene et al 2007).…”
Section: Arthropodsmentioning
confidence: 99%
“…However, the physiological functions regulated by FMRFamides and their receptors are largely unknown. Recently, a study suggests that FMRFamide-related peptides (FaRPs) may regulate circadian locomotor activity rhythms in the cockroach Leucophaea maderae (Soehler et al 2008 ) . Another study showed that one of abundant FMRFamides, DPKQDFMRFamide enhanced synaptic transmission through activation of FMRFamide receptor (FR) and myosupressin receptor-2 (DmsR-2) in D. melanogaster , which leads to enhanced fi ctive locomotion (Klose et al 2010 ) .…”
Section: Neuropeptide Gpcrsmentioning
confidence: 99%